‘Her Room Was Her World’: Nellie Sloggett and North Cornish Folklore - Simon Young (Journal of Ethnology and Folkloristics)
Nellie Sloggett (1850–1923) was a Cornish novelist and, under the name Enys Tregarthen, a folklore writer. This article has four aims. First, to bring together all the biographical information about Sloggett. Second, to make the point that Sloggett’s writing is useful for folklorists: she has, since her death, been neglected even by south-western scholars. Third, to situate her work in the broader British and Irish folklore movement: her corpus offers some unique challenges. And, fourth, to provide a hand-list of her books and her other writings to facilitate further research. It is hoped, too, that some of the reflections on the geography of folklore collection will have a wider application.